Moral Damages of Children's Migration Trauma (Based on The Materials of The International Internship in The Area of Education and Humanities) - Zhanna Virna; Ana Maria Eyng (Психологічне консультування i психотерапія)
The article is devoted to the theoretical analysis of moral damages of children's migration trauma in the context of the exchange of experience based on the materials of international internship. The purpose of the presented article is an analytical review of developments on the problem of trauma of the migration resocialization of children in the context of preserving mental health and children's rights (based on the materials of the scientific internship under the program of postgraduate education in the area of education and humanities, PUCPR, Curitiba, Brazil). It is based on the method of bibliographic review of theoretical and empirical sources on this problem and the method of psychological modelling as a reproduction of the functional content of moral damages of children's migration trauma. The results include the presentation of the methodological architectonics of the migration problem within the framework of the theory of intersectionality and the concept of social categorization. It is noted that the experience of Brazilian migration policy is focused on basic service of the needs of migrant children within the educational and psychological space. The scientific position of A.M. Eng in the study of children's rights in humanitarian situations and the cultivation of intercultural school programs is presented in detail. Psychological support in the cross-cultural situation of migration is specified and the consequences of moral conflicts for the child within the framework of ethnopsychoanalysis and socio-cognitive theories of post-traumatic stress disorder are substantiated. It is emphasized to take into account the vulnerability of the child in experiencing the moral trauma of migration. The factors of moral damages of the migration trauma of children and signs of risk to their mental health are determined. The dependence of children's moral damages on the identification experience and migration project of parents is substantiated. The clinical activity of Brazilian psychologists is focused on cross-cultural psychotherapy, which is based on the complementary basis of transcultural characteristics of adult migrants and their children. The conclusions indicate that within the framework of the international scientific internship in the field of education and humanities (PUCPR, Brazil), it was possible to get acquainted with psychological and educational research practices of working with migrant children. Similar interdisciplinary practices can be successfully applied in Ukraine, because the war and related migration, resettlement and refugees actualize the issues of intercultural education and the introduction of cross-cultural psychotherapy.